Physician deaths from corona virus (COVID-19) disease - Ing, E B (Occup Med (Lond), 2020)
BACKGROUND: The COVID-19 pandemic has caused much morbidity and mortality to patients but also health care providers. AIMS: We tabulated the cases of physician deaths from COVID-19 associated with front-line work in hopes of mitigating future events. METHODS: On 15 April 2020, a Google internet search was performed using the keywords ‘doctor’, ‘physician’, ‘death’, ‘COVID’ and ‘coronavirus’ in English and Farsi, and Chinese using the Baidu search engine. The age, sex and medical speciality of physicians who died from COVID-19 in the line of duty were recorded. Individuals greater than 90 years of age were excluded. RESULTS: We found 278 physicians who died with COVID-19 infection, but complete details were missing for 108 individuals. The average age of the physicians was 63.7 years with a median age of 66 years, and 90% were male (235/261). General practitioners and emergency room doctors (108/254), respirologists (5/254), internal medicine specialists (13/254) and anaesthesiologists (6/254) comprised 52% of those dying. Two per cent of the deceased were epidemiologists (5/254), 2% were infectious disease specialists (4/254), 6% were dentists (16/254), 4% were ENT (9/254) and 3% were ophthalmologists (8/254). The countries with the most reported physician deaths were Italy (121/278; 44%), Iran (43/278; 15%), Philippines (21/278; 8%), Indonesia (17/278; 6%), China (16/278; 6%), Spain (12/278; 4%), USA (12/278; 4%) and UK (11/278;4%). CONCLUSIONS: Physicians from all specialities may die from COVID. Lack of personal protective equipment was cited as a common cause of death. Consideration should be made to exclude older physicians from front-line work.